Financial sector transparency and net interest margins: Should the private or public sector lead financial sector transparency? - Baah Aye Kusi; Elikplimi Komla Agbloyor; Agyapomaa Gyeke-Dako; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study examines the effect of private and public sector led financial sector transparency on bank interest margins across eighty-six economies. Using a two-step dynamic system generalized method of moments, least square dummy variables, fixed effects and bootstrap quantile panel models between 2005 and 2016, the findings of the two-step GMM are reported as follows. First, results reveal that financial sector transparency whether led by private or public sector reduces interest margins. Second, while no statistical evidence was found on which of the two (private or public sector led transparency) is more effective in dealing with bank interest margins, public sector-led financial transparency is found to be more consistent in reducing bank interest margins across many more economies. Third, the study shows that the effect of financial sector transparency is visible at lower and middle levels of bank interest margins implying that economies with lower and moderately high bank interest margin level can benefit more from policies targeted at improving transparency in the financial sector. These findings imply that the sampled countries must enact policies and laws that deepen and expand financial sector transparency in order to potentially reduce bank interest margins for the good of banking market participants and society at large.
Keywords: 330; Financial Sector Transparency; Net Interest margins; Private Sector; Public Sector